The costs of living with elephants in the areas adjacent to Marsabit National Park and Reserve - Shadrack Ngene; Patrick Omondi (Pachyderm)
Crop raiding by elephants is a serious management problem around protected areas in Kenya. This is because of changes in the land use systems in these areas, with crop farming occurring in areas where it did not previously. Crop raiding by elephants was monitored in the area adjacent to Marsabit National Park and Reserve between August 2004 and July 2005 (excluding December 2004 and April 2005 due to rains). A total of 414 farms were raided, with the farmers loosing KES 15,034,610 (USD 208,814) during the period. Crop raiding was higher in August 2005 (KES 5,598,660 or USD 77,759) than in August 2004 (KES 503,960 or USD 6999). Tribal clashes in August 2005 contributed to unguarded farms and consequently elephants were presented with an opportunity to raid. The situation was peaceful in August 2004 and farmers had adequate time to guard their farms using scaring strategies to keep elephants away. There is an urgent need to revive the collapsed fence project in order to reduce the cost incurred by farmers due to elephants raiding their crops.